Expression and organization of BP74, a cyclic AMP-regulated gene expressed during Dictyostelium discoideum development. - Hopkinson, S B (1989)
We have characterized a cDNA and the corresponding gene for a cyclic AMP-inducible gene expressed during Dictyostelium development. This gene, BP74, was found to be first expressed about the time of aggregate formation, approximately 6 h after starvation. Accumulation of BP74 mRNA did not occur in Dictyostelium cells that had been starved in fast-shaken suspension cultures but was induced in similar cultures to which cyclic AMP pulses had been added. The BP74 cDNA and gene were characterized by DNA sequence analysis and transcriptional mapping. When the BP74 promoter region was fused with a chloramphenicol acetyltransferase reporter gene and reintroduced into Dictyostelium cells, the transfected chloramphenicol acetyltransferase gene displayed the same developmentally regulated pattern of expression as did the endogenous BP74 gene, suggesting that all of the cis-acting elements required for regulated expression were carried by a 2-kilobase cloned genomic fragment. On the basis of sequence analysis, the gene appeared to encode a protein containing a 20-residue hydrophobic sequence at the amino-terminal end and 26 copies of a 20-amino-acid repeat.